Supercharg3D : how 3D printing will drive your supply chain - Pannett, Len (John Wiley & Sons, Inc., 2019)
A strategic and operational guide to using 3D printing to drive value in the supply chain-featuring case studies and illustrated examples from across industries After many years as a tool for designers, 3D printing today promises to revolutionize supply chains. Cut through the hype and hyperbole, and it becomes clear that it offers unprecedented potential to redesign supply chain models, simplifying and shrinking them, enabling previously unimaginable designs to be produced where they are most needed. However, adopting it is a strategic endeavor, one that involves the consideration of several wider implications. This book goes beyond touting the latest technological advances or listing the many wonderful things that 3D printing is being used to make. It teaches readers what is important about 3D printing, why they need to prepare for its emergence today, and how they can go about adopting it. Supercharg3d: How 3D Printing Will Drive Your Supply Chain shows readers how to drive value in their supply chain by supercharging it-giving it more power-with 3D printing. Aimed at being a first reference for those in businesses who make strategic decisions on operations and supply chain matters, it takes a pragmatic position, balancing the opportunities that 3D printing presents with the reality of the limitations that it continues to have, so that readers can make the best decisions possible.-Strategic guide that covers 3D printing and its implications in the supply chain -Operational guidance and best practices for how and when 3D printing can be adopted -Identification of 3D printing's impacts on the individual SCOR supply chain elements -Features new, transformative supply chain models that are enabled by 3D printing -Includes case studies and illustrated examples from diverse industries including aerospace (Airbus), energy (Shell), consumer goods (Nike), medical (Align Technology) and transportation (Deutsche Bahn) Supercharg3d: How 3D Printing Will Drive Your Supply Chain is the go-to book for operations and supply chain decision makers in manufacturing, engineering and technology companies looking to incorporate the technology into their business operations.